2019
DOI: 10.1186/s13287-019-1249-2
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-335 regulates cardiac mesoderm and progenitor cell differentiation

Abstract: Background WNT and TGFβ signaling pathways play critical regulatory roles in cardiomyocyte fate determination and differentiation. MiRNAs are also known to regulate different biological processes and signaling pathways. Here, we intended to find candidate miRNAs that are involved in cardiac differentiation through regulation of WNT and TGFβ signaling pathways. Methods Bioinformatics analysis suggested hsa-miR-335-3p and hsa-miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Strikingly, lack of AMPKβ1 as well as AMPKβ2 showed major disturbances in this gene regulatory network, although to different extents. This is additionally confirmed by changes in the expression of specific miRNAs that are equally important for cardiac differentiation and physiology (26,(55)(56)(57), among others, altering the expression of cardiac transcription factors (58)(59)(60). While AMPKβ1-deficient hiPSCs maintain the ability to differentiate into CMs, lack of AMPKβ2 seems to abrogate it by attenuating the exit from pluripotency and the progression of differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…Strikingly, lack of AMPKβ1 as well as AMPKβ2 showed major disturbances in this gene regulatory network, although to different extents. This is additionally confirmed by changes in the expression of specific miRNAs that are equally important for cardiac differentiation and physiology (26,(55)(56)(57), among others, altering the expression of cardiac transcription factors (58)(59)(60). While AMPKβ1-deficient hiPSCs maintain the ability to differentiate into CMs, lack of AMPKβ2 seems to abrogate it by attenuating the exit from pluripotency and the progression of differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…31 MiRNAs as a class of small noncoding RNAs play a central role in cardiogenesis, heart function, and pathology. 32,33 It has been reported that miR-142 contributes to early cardiomyocyte differentiation of mouse ES cells, 34 miR-335 could regulate human cardiac mesoderm and progenitor cell differentiation, 35 whereas miR-130 acts as a necessary linkage for the negative Fgf8-Bmp2 feed-back as responsible to achieve early cardiac specification. 36 Our study found that in the process of differentiation of ES cells F I G U R E 4 MiR-184 inhibits cardiac mesoderm and cardiomyocyte differentiation of embryonic stem (ES) cells by targeting Wnt3.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNAs as an important hidden layer of regulation have pivotal roles in almost all biological processes. The ncRNAs can be classified based on their length into small (<200 nucleotides) and long noncoding RNAs (>200 nucleotides) [53][54][55].…”
Section: Noncoding Rnasmentioning
confidence: 99%